2019
DOI: 10.1039/c8nr08922a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of amphiphilic block copolymers in an aqueous solution: direct imaging of micelle formation and nanoparticle encapsulation

Abstract: In situTEM imaging reveals the dynamics of micelle formation and nanoparticle encapsulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 58 publications
3
44
0
Order By: Relevance
“…88,89 Liquid phase TEM has provided great insights into these processes through direct observations and quantitative analysis of the events in solution (Figure 3). 80,[85][86][87] Importantly, these observations were supported by complementary methods that help to address the question of "which features are representative," but also provide additional information to interpret the observed dynamics. Molecular dynamics simulations, 85,87 provide molecular-level details, which are not possible to obtain for soft matter, Gibbs free-energy calculations, 80 provide information on the thermodynamic driving forces, and x-ray scattering experiments, 86 provide information that is statistically robust.…”
Section: Biological and Soft Materialsmentioning
confidence: 82%
See 1 more Smart Citation
“…88,89 Liquid phase TEM has provided great insights into these processes through direct observations and quantitative analysis of the events in solution (Figure 3). 80,[85][86][87] Importantly, these observations were supported by complementary methods that help to address the question of "which features are representative," but also provide additional information to interpret the observed dynamics. Molecular dynamics simulations, 85,87 provide molecular-level details, which are not possible to obtain for soft matter, Gibbs free-energy calculations, 80 provide information on the thermodynamic driving forces, and x-ray scattering experiments, 86 provide information that is statistically robust.…”
Section: Biological and Soft Materialsmentioning
confidence: 82%
“…25,82 The self-assembly of block copolymers is an important process in soft-matter science as it can generate complex functional structures that find application in medicine and catalysis. 83,84 Despite being studied for decades, there have been great challenges in understanding the role that phase separation, 80 particles fusion 85 and fission, 86 and encapsulation 87 play in the formation of complex structures. 88,89 Liquid phase TEM has provided great insights into these processes through direct observations and quantitative analysis of the events in solution (Figure 3).…”
Section: Biological and Soft Materialsmentioning
confidence: 99%
“…30 In a similar manner, sub-1 µm liposomes could be used as electron-transparent vessels for controlling and imaging nanoscale reactions in TEM liquid cells. Towards the latter objective, empty liposomes 50 to 300 nm in diameter, [39][40][41] along with other soft colloids like polymeric micelles 42,43 and vesicles, 44 have been imaged with liquid cell TEM. Due to potential electron beam damage, however, it remains a challenge to utilize these soft colloids as nanoreactors for hosting reactions for high resolution in situ TEM imaging.…”
Section: Main Textmentioning
confidence: 99%
“…This is consistent with other reports that observed soft materials only under low-dose conditions, with typical dose rates below 10 e -Å -2 s -1 . 12,40,[42][43][44]50 Under such low-doses, it is difficult to achieve sufficient image contrast to resolve reaction dynamics inside the liposomes with high spatial and temporal resolution. 51 We increased the number of observable liposomes by constructing cells from carbon membranes 18,19 (Figure 1a), hypothesizing that they could offer more favorable substrates for liposomes compared to graphene liquid cells while retaining the electron transparency of graphene.…”
Section: Main Textmentioning
confidence: 99%
“…Among the various nanomaterials for preparing drug delivery systems, amphiphilic polysaccharide derivatives have been widely used in biomedical applications such as efficient encapsulation and targeted delivery of drugs, because of their good cytocompatibility and biodegradability [14][15][16][17]. It has been found that amphiphilic block or graft copolymers can form various types of self-assembled, stable, nano-sized micellar aggregates in aqueous solution [18,19]. Due to their biosafety and biodegradable character, self-assembled nanoparticles such as lipid, polylactic-co-glycolic acid (PLGA), polyamidoamine (PAMAM) dendrimers and polysaccharide based nanoparticles consisting of an internal hydrophobic core and an externally surrounded hydrophilic group, have been widely reported to increase the delivery efficiency and bioavailability of drugs [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%